1987
DOI: 10.1126/science.238.4832.1415
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Cold-Hardening Process in Insects

Abstract: Traditionally studies of cold tolerance in insects have focused on seasonal adaptations related to overwintering that are observed after weeks or months of exposure to low temperature. In contrast, an extremely rapid cold-hardening response was observed in nonoverwintering stages that confers protection against injury due to cold shock at temperatures above the supercooling point. This response was observed in nondiapausing larvae and pharate adults of the flesh fly, Sarcophaga crassipalpis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
295
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 423 publications
(310 citation statements)
references
References 8 publications
10
295
0
Order By: Relevance
“…Although RCH has been described in many species, the mechanisms are not well understood (Chown and Nicholson, 2004). Lee et al (1987) found an increase in concentration of the common carbohydrate cryoprotectant glycerol after 0 °C pre-treatments in the flesh fly (Sarcophaga crassipalpis) to 81.3 mM, nearly three times the levels found in prechilled organisms. Although the changes were not large enough to have a colligative effect (i.e.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although RCH has been described in many species, the mechanisms are not well understood (Chown and Nicholson, 2004). Lee et al (1987) found an increase in concentration of the common carbohydrate cryoprotectant glycerol after 0 °C pre-treatments in the flesh fly (Sarcophaga crassipalpis) to 81.3 mM, nearly three times the levels found in prechilled organisms. Although the changes were not large enough to have a colligative effect (i.e.…”
Section: Introductionmentioning
confidence: 87%
“…A number of insects that suffer from non-freezing cold injury are nevertheless able to rapidly alter their tolerance of acute cold exposure by rapid cold-hardening (RCH; Lee et al, 1987), whereby low temperature tolerance is greatly enhanced by a short pre-exposure to a milder low temperature. For example, Czajka and Lee (1990) showed that adult Drosophila melanogaster will die (but not freeze) when exposed to −5 °C for 2 h, but if chilled at 5 °C for as little as 2 h prior to the subzero treatment, most will survive.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we measured whether capa knockdown impacts acute cold shock tolerance, the capacity for rapid cold hardening (RCH), and chill coma recovery time (CCR). RCH is an extreme case of rapid acclimation whereby brief (minutes to hours) nonlethal chilling significantly enhances cold-shock tolerance (35). CCR is a commonly used assay to assess the time required to regain coordinated movement after nonlethal chilling injury and frequently is used as an indicator of cold tolerance, especially in Drosophila species (16,36).…”
Section: Capa Neuropeptides Are Released Not During Desiccation and Coldmentioning
confidence: 99%
“…Physiological studies in various organisms show that mild stress can increase the hardiness of the organism to the same but harsher stress (Bowler, 2005). Rapid Cold Hardening (RCH), an increase in cold tolerance after a prior (sub-lethal) exposure to cold, first described by Lee et al (1987) has been observed in numerous insect groups (Meats, 1973;Chown and Terblanche, 2007) including isolated tissue and cells (Yi and Lee, 2003).…”
Section: Introductionmentioning
confidence: 99%